E-way drive thru shopping / Aidatul Syamimi Mohd Tajudin, Nur Sharmila Sabri and Nurul Ayuni Mohd Azmi - Mohd Tajudin, Aidatul Syamimi; Sabri, Nur Sharmila; Mohd Azmi, Nurul Ayuni (2018)
In business of technology, a new product development (NPD) is the complete process of bringing a new product to market. A product is a set of benefits offered for exchange and can be tangible that is something physical you can touch or intangible like a service, experience, or belief. There are two parallel paths involved in the NPD process is one involves the idea generation, product design and detail engineering the other involves market research and marketing analysis. Companies typically see new product development as the first stage in generating and commercializing new product within the overall strategic process of product life cycle management used to maintain or grow their market share. The findings draw attention to the fact that problems in shopping hypermarket shows some major and minor problem. Firstly, this study come out with the problems and issues. Next, identifying the solutions to solve this problems with a methodology and process of new product development (NPD). In a conclusion, this new product development will be evaluating this range and concludes that it would be an ideal candidate to meet the challenge presented by the application and could satisfy the shoppers needed. The drive thru shopping can be a successfully new product development and can be as the process by which entrepreneur designs and creates new product or service that will be sold to customers.